Survival and Prognosis for Patients with Rectal Melanomas in the United States: A SEER-Based Study - Fan Zhang; Boqi Xu; Yao Peng; Runda Wu; Shan Tong; Zhongqi Mao (Journal of Investigative Surgery)
Purpose Limited attention was paid to focus on rectal melanomas (RM). This study aimed to evaluate the survival rate and prognostic factors of RM.Methods The data for patients with RM from Surveillance, Epidemiology, and End Results (SEER) database were used to analyze tumor survival. Kaplan-Meier method and log-rank test were employed to estimate cancer-specific survival (CSS) and overall survival (OS). A nomogram was established based on the risk factors of survival by the forest plot for multivariate Cox regression analysis. Receiver operating characteristic (ROC) and calibration curve were conducted for validation.Results A total of 187 patients with RM were selected to perform survival analyses. The median survival time of OS was 12 months (range: 0-146 months), and the median survival time of CSS was 12 months (range: 0-74 months). Patients’ age, tumor size, stage, the number of nodes examined, surgery, and radiation were identified as prognostic indicators for CSS by the forest plot for multivariate Cox regression analysis. The nomogram was validated as a reliable model for CSS.Conclusion Clinicopathologic relevance with tumor prognosis was confirmed in this study. Our nomogram can provide a relatively accurate prediction of the survival rate of patients with RM.